Validity and reliability of global positioning system units (STATSports Viper) for measuring distance and peak speed in sports - Beato, M.; Devereux, G.; Stiff, A. (The Journal of Strength and Conditioning Research, 2018)
Previous evidence has proven that large variability exists in the accuracy of different brands of global positioning systems (GPS). Therefore, any GPS model should be validated independently, and the results of a specific brand cannot be extended to others. The aim of this study is to assess the validity and reliability of GPS units (STATSports Viper) for measuring distance and peak speed in sports. Twenty participants were enrolled (age 21 ± 2 years [range 18 to 24 years], body mass 73 ± 5 kg, and height 1.78 ± 0.04 m). Global positioning system validity was evaluated by comparing the instantaneous values of speed (peak speed) determined by GPS (10 Hz, Viper Units; STATSports, Newry, Ireland) with those determined by a radar gun during a 20-m sprint. Data were analyzed using the Stalker (34.7 GHz, USA) ATS Version 5.0.3.0 software as gold standard. Distance recorded by GPS was also compared with a known circuit distance (400-m running, 128.5-m sports-specific circuit, and 20-m linear running). The distance bias in the 400-m trial, 128.5-m circuit, and 20-m trial was 1.99 ± 1.81%, 2.7 ± 1.2%, and 1.26 ± 1.04%, respectively. Peak speed measured by the GPS was 26.3 ± 2.4 km/h, and criterion was 26.1 ± 2.6 km/h, with a bias of 1.80 ± 1.93%. The major finding of this study was that GPS did not underestimate the criterion distance during a 400-m trial, 128.5-m circuit, and 20-m trial, as well as peak speed. Small errors (<5%, good) were found for peak speed and distances. This study supported the validity and reliability of this GPS model.